Playing with covalent triazine framework tiles for improved CO2 adsorption properties and catalytic performance - Tuci, Giulia; Iemhoff, Andree; Ba, Housseinou; Luconi, Lapo; Rossin, Andrea; Papaefthimiou, Vasiliki; Palkovits, Regina; Artz, Jens; Pham-Huu, Cuong; Giambastiani, Giuliano (Beilstein Journal of Nanotechnology, 2019)
The rational design and synthesis of covalent triazine frameworks (CTFs) from defined dicyano-aryl building blocks or their binary mixtures is of fundamental importance for a judicious tuning of the chemico-physical and morphological properties of this class of porous organic polymers. In fact, their gas adsorption capacity and their performance in a variety of catalytic transformations can be modulated through an appropriate selection of the building blocks. In this contribution, a set of five CTFs (CTF1–5) have been prepared under classical ionothermal conditions from single dicyano-aryl or heteroaryl systems. The as-prepared samples are highly micro-mesoporous and thermally stable materials featuring high specific surface area (up to 1860 m2·g−1) and N content (up to 29.1 wt %). All these features make them highly attractive samples for carbon capture and sequestration (CCS) applications. Indeed, selected polymers from this series rank among the CTFs with the highest CO2 uptake at ambient pressure reported so far in the literature (up to 5.23 and 3.83 mmol·g−1 at 273 and 298 K, respectively). Moreover, following our recent achievements in the field of steam- and oxygen-free dehydrogenation catalysis using CTFs as metal-free catalysts, the new samples with highest N contents have been scrutinized in the process to provide additional insights to their complex structure–activity relationship.
Keywords: covalent triazine frameworks; CO2 adsorption; CO2/N2 selectivity; dehydrogenation catalysis; ionothermal conditions

(untitled) - Dai, L.; Chang, D. W.; Baek, J.-B.; Lu, W. (Small, 2012)

(untitled) - De Volder, M. F. L.; Tawfick, S. H.; Baughman, R. H.; Hart, A. J. (Science, 2013)

(untitled) - Zhang, Q.; Uchaker, E.; Candelaria, S. L.; Cao, G. (Chem. Soc. Rev., 2013)

(untitled) - Thomas, A. (Angew. Chem., Int. Ed., 2010)

(untitled) - Vilela, F.; Zhang, K.; Antonietti, M. (Energy Environ. Sci., 2012)

(untitled) - Rose, M. (ChemCatChem, 2014)

(untitled) - Chaoui, N.; Trunk, M.; Dawson, R.; Schmidt, J.; Thomas, A. (Chem. Soc. Rev., 2017)

(untitled) - Rogge, S. M. J.; Bavykina, A.; Hajek, J.; Garcia, H.; Olivos-Suarez, A. I.; Sepúlveda-Escribano, A.; Vimont, A.; Clet, G.; Bazin, P.; Kapteijn, F.; Daturi, M.; Ramos-Fernandez, E. V.; et al. (Chem. Soc. Rev., 2017)

(untitled) - Dawson, R.; Cooper, A. I.; Adams, D. J. (Prog. Polym. Sci., 2012)

(untitled) - Xu, Y.; Jin, S.; Xu, H.; Nagai, A.; Jiang, D. (Chem. Soc. Rev., 2013)

(untitled) - Zou, X.; Ren, H.; Zhu, G. (Chem. Commun., 2013)

(untitled) - Puthiaraj, P.; Lee, Y.-R.; Zhang, S.; Ahn, W.-S. (J. Mater. Chem. A, 2016)

(untitled) - Artz, J. (ChemCatChem, 2018)

(untitled) - Kuhn, P.; Antonietti, M.; Thomas, A. (Angew. Chem., Int. Ed., 2008)

(untitled) - Kuhn, P.; Thomas, A.; Antonietti, M. (Macromolecules, 2009)

(untitled) - Sakaushi, K.; Hosono, E.; Nickerl, G.; Zhou, H.; Kaskel, S.; Eckert, J. (J. Power Sources, 2014)

(untitled) - Talapaneni, S. N.; Hwang, T. H.; Je, S. H.; Buyukcakir, O.; Choi, J. W.; Coskun, A. (Angew. Chem., Int. Ed., 2016)

(untitled) - Liu, J.; Zan, W.; Li, K.; Yang, Y.; Bu, F.; Xu, Y. (J. Am. Chem. Soc., 2017)

(untitled) - Hug, S.; Mesch, M. B.; Oh, H.; Popp, N.; Hirscher, M.; Senker, J.; Lotsch, B. V. (J. Mater. Chem. A, 2014)

(untitled) - Dey, S.; Bhunia, A.; Esquivel, D.; Janiak, C. (J. Mater. Chem. A, 2016)

(untitled) - Dey, S.; Bhunia, A.; Breitzke, H.; Groszewicz, P. B.; Buntkowsky, G.; Janiak, C. (J. Mater. Chem. A, 2017)

(untitled) - Artz, J.; Delidovich, I.; Pilaski, M.; Niemeier, J.; Kübber, B. M.; Rahimi, K.; Palkovits, R. (RSC Adv., 2018)

(untitled) - Artz, J.; Mallmann, S.; Palkovits, R. (ChemSusChem, 2015)

(untitled) - Artz, J.; Palkovits, R. (ChemSusChem, 2015)

(untitled) - Bavykina, A. V.; Goesten, M. G.; Kapteijn, F.; Makkee, M.; Gascon, J. (ChemSusChem, 2015)

(untitled) - Chan-Thaw, C. E.; Villa, A.; Wang, D.; Santo, V. D.; Orbelli Biroli, A.; Veith, G. M.; Thomas, A.; Prati, L. (ChemCatChem, 2015)

(untitled) - Katekomol, P.; Roeser, J.; Bojdys, M.; Weber, J.; Thomas, A. (Chem. Mater., 2013)

(untitled) - Palkovits, R.; Antonietti, M.; Kuhn, P.; Thomas, A.; Schüth, F. (Angew. Chem., Int. Ed., 2009)

(untitled) - Pilaski, M.; Artz, J.; Islam, H.-U.; Beale, A. M.; Palkovits, R. (Microporous Mesoporous Mater., 2016)

(untitled) - Tuci, G.; Pilaski, M.; Ba, H.; Rossin, A.; Luconi, L.; Caporali, S.; Pham-Huu, C.; Palkovits, R.; Giambastiani, G. (Adv. Funct. Mater., 2017)

Microporous Framework Solids - Wright, P. A. (Royal Society of Chemistry, 2008)

(untitled) - Ben, T.; Pei, C.; Zhang, D.; Xu, J.; Deng, F.; Jing, X.; Qiu, S. (Energy Environ. Sci., 2011)

(untitled) - Hug, S.; Stegbauer, L.; Oh, H.; Hirscher, M.; Lotsch, B. V. (Chem. Mater., 2015)

(untitled) - Ba, H.; Liu, Y.; Truong-Phuoc, L.; Duong-Viet, C.; Nhut, J.-M.; Nguyen, D. L.; Ersen, O.; Tuci, G.; Giambastiani, G.; Pham-Huu, C. (ACS Catal., 2016)

(untitled) - Zhao, Z.; Dai, Y.; Lin, J.; Wang, G. (Chem. Mater., 2014)

(untitled) - Zhao, Z.; Dai, Y. (J. Mater. Chem. A, 2014)

(untitled) - Zhao, Z.; Dai, Y.; Ge, G.; Guo, X.; Wang, G. (Green Chem., 2015)

(untitled) - Zhao, Z.; Dai, Y.; Ge, G. (Catal. Sci. Technol., 2015)

(untitled) - Ba, H.; Liu, Y.; Mu, X.; Doh, W.-H.; Nhut, J.-M.; Granger, P.; Pham-Huu, C. (Appl. Catal., A, 2015)

(untitled) - Zhang, J.; Su, D. S.; Blume, R.; Schlögl, R.; Wang, R.; Yang, X.; Gajović, A. (Angew. Chem., Int. Ed., 2010)

(untitled) - Zhao, Z.; Dai, Y.; Ge, G.; Wang, G. (ChemCatChem, 2015)

(untitled) - Liu, H.; Diao, J.; Wang, Q.; Gu, S.; Chen, T.; Miao, C.; Yang, W.; Su, D. (Chem. Commun., 2014)

(untitled) - Wang, R.; Sun, X.; Zhang, B.; Sun, X.; Su, D. (Chem. – Eur. J., 2014)

(untitled) - Zhao, Z.; Dai, Y.; Ge, G.; Wang, G. (AIChE J., 2015)

(untitled) - Thommes, M.; Kaneko, K.; Neimark, A. V.; Olivier, J. P.; Rodriguez-Reinoso, F.; Rouquerol, J.; Sing, K. S. W. (Pure Appl. Chem., 2015)

(untitled) - Wang, K.; Huang, H.; Liu, D.; Wang, C.; Li, J.; Zhong, C. (Environ. Sci. Technol., 2016)

(untitled) - Schwinghammer, K.; Hug, S.; Mesch, M. B.; Senker, J.; Lotsch, B. V. (Energy Environ. Sci., 2015)

(untitled) - Bhunia, A.; Vasylyeva, V.; Janiak, C. (Chem. Commun., 2013)

(untitled) - Osadchii, D. Y.; Olivos-Suarez, A. I.; Bavykina, A. V.; Gascon, J. (Langmuir, 2017)

(untitled) - Zhu, X.; Tian, C.; Veith, G. M.; Abney, C. W.; Dehaudt, J.; Dai, S. (J. Am. Chem. Soc., 2016)

(untitled) - Mukherjee, S.; Das, M.; Manna, A.; Krishna, R.; Das, S. (J. Mater. Chem. A, 2019)

(untitled) - Zhao, Y.; Yao, K. X.; Teng, B.; Zhang, T.; Han, Y. (Energy Environ. Sci., 2013)

(untitled) - Yuan, K.; Liu, C.; Zong, L.; Yu, G.; Cheng, S.; Wang, J.; Weng, Z.; Jian, X. (ACS Appl. Mater. Interfaces, 2017)

(untitled) - Park, K.; Lee, K.; Kim, H.; Ganesan, V.; Cho, K.; Jeong, S. K.; Yoon, S. (J. Mater. Chem. A, 2017)

(untitled) - Fu, Y.; Wang, Z.; Li, S.; He, X.; Pan, C.; Yan, J.; Yu, G. (ACS Appl. Mater. Interfaces, 2018)

(untitled) - Yuan, K.; Liu, C.; Liu, C.; Zhang, S.; Yu, G.; Yang, L.; Yang, F.; Jian, X. (Polymer, 2018)

(untitled) - Jena, H. S.; Krishnaraj, C.; Wang, G.; Leus, K.; Schmidt, J.; Chaoui, N.; Van Der Voort, P. (Chem. Mater., 2018)

(untitled) - Lee, Y. J.; Talapaneni, S. N.; Coskun, A. (ACS Appl. Mater. Interfaces, 2017)

(untitled) - Wang, G.; Leus, K.; Zhao, S.; Van Der Voort, P. (ACS Appl. Mater. Interfaces, 2018)

(untitled) - Wang, G.; Leus, K.; Jena, H. S.; Krishnaraj, C.; Zhao, S.; Depauw, H.; Tahir, N.; Liu, Y.-Y.; Van Der Voort, P. (J. Mater. Chem. A, 2018)

(untitled) - Du, J.; Liu, Y.; Krishna, R.; Yu, Y.; Cui, Y.; Wang, S.; Liu, Y.; Song, X.; Liang, Z. (ACS Appl. Mater. Interfaces, 2018)

(untitled) - Zhu, X.; Mahurin, S. M.; An, S.-H.; Do-Thanh, C.-L.; Tian, C.; Li, Y.; Gill, L. W.; Hagaman, E. W.; Bian, Z.; Zhou, J.-H.; Hu, J.; Liu, H.; et al. (Chem. Commun., 2014)

(untitled) - Bae, Y.-S.; Snurr, R. Q. (Angew. Chem., Int. Ed., 2011)

(untitled) - Haszeldine, R. S. (Science, 2009)

(untitled) - Liebl, M. R.; Senker, J. (Chem. Mater., 2013)

(untitled) - Zhao, Z.; Dai, Y.; Ge, G.; Mao, Q.; Rong, Z.; Wang, G. (ChemCatChem, 2015)

(untitled) - Kissin, Y. V. (Catal. Rev.: Sci. Eng., 2001)

(untitled) - Jin, X.; Balasubramanian, V. V.; Selvan, S. T.; Sawant, D. P.; Chari, M. A.; Lu, G. Q.; Vinu, A. (Angew. Chem., Int. Ed., 2009)

(untitled) - Gounder, R.; Iglesia, E. (J. Am. Chem. Soc., 2009)

(untitled) - Dey, S.; Bhunia, A.; Boldog, I.; Janiak, C. (Microporous Mesoporous Mater., 2017)

(untitled) - Schell, J.; Casas, N.; Pini, R.; Mazzotti, M. (Adsorption, 2012)